The spirit of manufacturing excellence : - Huge, Ernest C. (Dow Jones-Irwin, 1988)
In this aptly titled book Ernest Huge makes the point that world-class manufacturing is a guiding philosophy of enlightened leadership. All too often, Total Quality Management, Just in Time, Six Sigma, and Lean Manufacturing are presented as nothing more than a series of acronyms, tools, and techniques. Huge goes much deeper, and in so doing rightly characterizes the steep and narrow road to transformation of the workplace. Only 111 pages long, The Spirit of Manufacturing Excellence is filled with simple yet profound wisdom. Just as one of the foundations of world-class operations is the elimination from the process of everything that is not essential, so the author has focused on the essence of best manufacturing practice. Every concept and idea that is presented adds value for the reader.